Hoabinhian and Austronesia: The Root of Diversity in the Western Part of Indonesia - Wiradnyana, Ketut (European Scientific Journal, ESJ, 2016)
The western part of Indonesia mentioned in this paper includes the provinces of North Sumatera and Aceh, in the northern part of Sumatera. The two provinces are rich in archaeological remains, particularly those from Early Holocene up to the megalithic culture. Human activities during the Early Holocene were characterized by the presence of Kitchen Midden sites and Austromelanesoids with Hoabinh culture. This culture is commonly found along the east coast of the two provinces, and some of them are on highlands. The Neolithic culture, which contributes highly significant Austronesian data, are found at the sites on highland area, while other cultures from later period contribute the Megalithic culture that continues until now and becomes the living tradition. The entire depiction is the achievement from a series of archaeological researches, which in turn describes the mixing process among humans and their cultures. The result is a diversity of Indonesian people, particularly in the western part of Indonesia.